2021
DOI: 10.3947/ic.2020.0142
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus is Hyperendemic in Nigeria from 2009 to 2020: A Contemporary Systematic Review

Abstract: Backround Data on Dengue virus (DENV) infection prevalence, geographic distribution and risk factors are necessary to direct appropriate utilization of existing and emerging control strategies. This study aimed to determine the pooled prevalence, risk factors of DENV infection and the circulating serotypes within Nigeria from January 1, 2009 to December 31, 2020. Materials and methods Twenty-one studies out of 2,215 available articles were eligible and included for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Our findings suggested that the risk of dengue infection may be related to several maternal demographic characteristics including age, occupation, education, and income level, which is consistent with previous studies (41)(42)(43). Pregnant women with an older age may be more likely exposed to dengue virus over time (41).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggested that the risk of dengue infection may be related to several maternal demographic characteristics including age, occupation, education, and income level, which is consistent with previous studies (41)(42)(43). Pregnant women with an older age may be more likely exposed to dengue virus over time (41).…”
Section: Discussionsupporting
confidence: 89%
“…As a result, several factors, including poor housing favouring mosquito breeding habitats, uncontrolled urbanisation, cultural and behavioural practices resulting in poor sewage and drainage infrastructures, and unhygienic conditions of the environment, were compounded by the unwholesome location of waste disposal dumpsites close to various homes in slums and urban areas in the study regions. Rural–urban migration, expansion of agricultural activities to sylvatic areas in rural settings, and political and conflict fatigue may also be the drivers of these high seroprevalences in the three regions [ 8 , 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary vectors often have relatively little contact with humans and may be less susceptible to residual insecticide spraying or insecticide-impregnated bednets than primary vectors [ 7 ]. There is an increased risk of chikungunya and malaria occurring concurrently and causing malaria and nonmalaria febrile illnesses [ 11 , 12 , 13 ]. Chikungunya and malaria can also coexist in areas where the two vectors are present [ 4 , 8 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]; therefore, super- or coinfection is a possibility.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most cases of dengue fever are misdiagnosed as malaria or typhoid fever in most healthcare facilities [20]. In Nigeria, dengue fever is endemic in almost all states and may be the leading cause of unclassified febrile illness [21]. Dengue fever has a different prevalence in urban and rural areas and has been reported predominantly in urban areas rather than rural areas [21].…”
Section: N Results and Discussionmentioning
confidence: 99%